In memory of Professor Korniy Denisovich Tovstyuk - ojsadmin, ojsadmin (Physics and Chemistry of Solid State, 2019)
Doctor of Physical and Mathematical Sciences, corresponding member of NAS of Ukraine, twice laureate of the State Prize of Ukraine in the field of science and technology